PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK BERBASIS PROBLEM BASED LEARNING MATEMATIKA SMP PADA MATERI SUDUT - Sarassanti, Yumi (Uninus Journal of Mathematics Education and Science (UJMES), 2024)
This research aims to produce LKPD based on Problem-Based Learning (PBL) for junior high school mathematics. This development research adopts the ADDIE development model with stages including Analysis, Design, Development, Implementation, and Evaluation. The quality of the LKPD is reviewed from the assessment of material experts, media experts, and student responses. The research instruments used were a material expert questionnaire, a media expert questionnaire, and a student response questionnaire. The LKPD was tested in class VII MTS Mujahidin with 32 students as subjects. The LKPD developed contains learning activities according to PBL steps, presents problems related to daily life at the beginning of learning, and can be used in learning. Judging from the material aspect, the LKPD is assessed as good with an average assessment score by material experts of 4.00. Judging from the media aspect, the LKPD is considered good with an assessment score by media experts of 3.60. Students' responses to the use of LKPD are included in the good category with an average assessment score of 4.05. It can be concluded that the PBL-based LKPD for class VII junior high school is suitable for use in implementing mathematics learning.   Keywords: Development, , Problem Based Learning, Student Worksheets